Inhibition of Galectin-1 attenuates lung fibroblast activation and proliferation in lung fibrosis: Galectin-1 inhibition attenuates acute lung fibrosis - Xue, Jing; Li, Shaojun (Cellular and Molecular Biology, 2023)
The purpose of this study was to investigate the parenchymal changes in idiopathic pulmonary fibrosis (IPF) caused by massive fibroblastic infiltration and proliferation in lung tissue. Galectin-1 (Gal-1) has been reported to be involved in angiogenesis and fibrosis via modification of TGF-b receptor signaling pathways. However, it remains unknown whether Galectin-1 plays a critical role in IPF. In the current study, we aimed to identify Gal-1 as a crucial fibrotic protein in IPF process. Murine lung fibroblast was pre-treated using Gal-1 inhibitor OTX-008 or overexpression of Gal-1 and then activated using transforming growth factor-beta (TGF-β). Adult male C57BL/6J mice were conducted intratracheal injection of bleomycin (BLM) for lung fibrosis. Mice were conducted OTX-008 administration. Gal-1 expression, fibroblast activation and proliferation, extracellular matrix (ECM), lung fibrosis, lung histology and pulmonary function were investigated respectively. We demonstrated that Gal-1, as a positive pro-fibrotic marker, could promote lung fibroblast activation and proliferation. Inhibition of Gal-1 reduced fibroblast activation and proliferation through negative regulation of TGF-β/Erk1/2 and AKT pathway. In vivo, Gal-1 inhibition ameliorates lung fibroblast accumulation and protects lung histology and function. Gal-1 is verified to be a pro-fibrotic gene in IPF pathogenesis, which promotes fibroblast activation and proliferation via TGF-β/Erk1/2 and AKT pathway. Moreover, inhibition of Gal-1 in lung fibrosis model attenuates lung fibroblast bioactivity and reduces ECM, leading to improved pulmonary histology and function. Hence, knockdown of Gal-1 in IPF may be a promising target therapy.